Implementasi Dokumen Mutu untuk Penurunan Cacat Produksi Sambal Andaliman dalam Botol - Iwan Makhmul Rambe; Eko Hari Purnomo (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2021)
One of the problems faced during production of bottled andaliman chilli sauce is production defect. The main factor causing this problem is the absence of quality documents that regulates stan-dardization of processes applied in the production division. This research aims to compile quality documents consisting of standard operating procedures (SOP) and work instructions (WI) as guidelines in the production process and evaluate the application of SOP and WI to the defect rate of final product. This research consists of five stages, identification the condition of production facilities at CV XYZ, pre-paration of quality documents, socialization in the production division, evaluation of quality documents for products, and implementation in the production division. In this study, quality documents in the form of SOP and WI were designed based on field observations, employee interviews, and company quality records. The results of this study indicate that the application of quality documents can reduce defective products by 8.56% in one production batch. The company’s losses due to defective products can be reduced by 15.42 million rupiah per month from the total production of 6000 jars.